An Online Recommender Agent for Boosting the Confidence of an e-learner - Bhattacharya, S; Chowdhury, S; Roy, S (International Journal of Computer Sciences and Engineering, 2014)
In online learning environment learners often face different types of problem due to physical absence of teacher. One of the major problems is losing the self-confidence in e-learning environment. In this paper an online recommender agent is proposed for boosting the confidence of e-learner. The designed and developed system has the ability to predict the level of confidence as well as knowledge of an e-learner through some evaluation procedure. According to the various levels of confidence and knowledge, system will provide several recommendations with the intention to enhance the confidence of the e-learner. A prototype has been developed based on the proposed system and applied on some students from eleven grade of CBSE board, India. The response obtained indicates that the system is able to raise the confidence of e-learner.